Administrative and curricular reforms in the U.P. College of Education reactions of Manila public secondary school teachers - De la Fuente, Zosima (Santos) 192- ([Quezon City s.n.], 1974)
This is a survey of the reactions of teachers to the proposed curricular reforms in the U.P. College of Education. Specifically, this paper determined the reactions of Manila public high school teachers to the proposed institution of night and/or Saturday classes, Plan "A" and Plan "B" Masteral Programs and Professional Diploma Programs at the U.P. College of Education.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Philippines. University -- College of Education; Teachers -- Manila